Drug Prevention Outreach: Enhancing Youth Knowledge and Awareness in Ureng Country, Maluku Tengah, Indonesia - Fransina S Latumahina; Anshari Betekeneng; Dandi Alvian Hakim; Arman Wally; Ari Fisal Waelissa (Indonesian Journal of Cultural and Community Development, 2023)
The dangers and detrimental effects of drugs on the lives and health of addicts and their families have become increasingly concerning. This study aimed to address the lack of understanding about narcotics among the youth in Ureng Country, which consists mostly of vulnerable individuals susceptible to drug contamination. The research was conducted through a community engagement initiative called the "Kuliah Kerja Nyata" (KKN) or Community Service Learning program, in collaboration with the National Narcotics Agency of Maluku Province. The drug prevention outreach involved a socialization program targeting 30 young people in Ureng Country. The implementation of the program consisted of several stages, including obtaining permission, preparation, conducting the socialization event, engaging in a question-and-answer session, and concluding with closing remarks and prayers. The results demonstrated that the drug prevention outreach successfully increased the youth's knowledge and awareness regarding the detrimental effects of drugs and drug abuse. The implications of this study highlight the importance of community-based initiatives in tackling drug-related issues, particularly among the younger generation, and call for further research and interventions to combat drug abuse globally.Highlight: Dual nature of drugs: Drugs can provide benefits but also pose health risks, including addiction. Negative impacts: Drugs affect individuals, families, and communities, leading to deviant behavior and future generation damage. Importance of drug prevention: Knowledge counseling and socialization programs help increase youth awareness and prevent drug abuse. Keyword:Drugs, Narcotics, Drug Prevention, Youth, Knowledge